Großerzählungen des Extremen Neue Rechte, Populismus, Islamismus, War on Terror - Schellhöh, Jennifer; Reichertz, Jo; Heins, Volker M.; Flender, Armin (X-Texte zu Kultur und Gesellschaft, 2018)
What makes radical world views so attractive? And how can the revival of extremism be explained from the perspective of cultural and social studies? If major narratives were supposed to be found on the dump of history, they have lately found their way back into the discourse with the return of fundamentalism. The contributions in this book introduce mental figures and forms of rhetoric, symbolism and forms of behavior contained in various major narratives of extremes, and they discuss how the Western world embeds them in its own tale.